Can inflammation parameters be determinant in upper level lumbar disc hernias? - Satis, Serap; Yetisgin, Alparslan; Burak Ethemoglu, Kadri (Annals of Medical Research, 2021)
Aim: Upper lumbar disc hernias are disc hernias located at the L1–L2, L2–L3, and L3–L4 levels. Upper lumbar disc hernias make up approximately 5% of herniated lumbar discs. The etiology of upper lumbar disc hernias is unclear. We investigated the relationship between hemogram values, sedimentation, C-reactive protein values and upper lumbar disc hernias.Materials and Methods: Patients were divided into three groups: Group 1 (61 patients with upper lumbar disc hernias), Group 2 (96 patients with lower level lumbar disc hernias), and Group 3 (40 patients without disc hernias). Gender, age, serum hemogram parameters, including white blood cell, lymphocyte, neutrophil, monocyte, mean platelets volume, plateletss, red cell distribution width, neutrophil-to-lymphocyte ratio, platelets-to-lymphocyte ratio, sedimentation and C-reactive protein values were obtained from the system and recorded. Patients; Acute pain ( 3 months) was evaluated.Results: The group with upper lumbar disc hernias (Group 1) had the highest mean age; there were also statistically significant differences between Group 1 and Group 2 and between Group 2 and Group 3 in terms of age (p 0.05 and p = 0.021, respectively). There were no significant differences between groups in terms of gender, hemogram parameters, sedimentation and C-reactive protein values, neutrophil-to-lymphocyte ratio or platelets-to-lymphocyte ratio. Groups were also evaluated for acute, subacute and chronic pain, and there were no significant differences between groups.Conclusion: We concluded that hemogram parameters (white blood cell count, lymphocyte count, neutrophil count, monocytes, red cell distribution width, mean platelets volume and platelets count), sedimentation and C-reactive protein values, neutrophil-to-lymphocyte ratio and platelets-to-lymphocyte ratio are not indicators for diagnosis of upper lumbar disc hernias.